2017
DOI: 10.1080/07357907.2016.1254228
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-196a as a Potential Diagnostic Biomarker for Esophageal Squamous Cell Carcinoma

Abstract: We observed significant up-regulation of miR-196a in esophageal squamous cell carcinoma (ESCC) as compared with their adjacent normal tissue (p = .002). Receiver operating characteristics curve analysis confirmed the suitability of miR-196a as a potential tumor marker for diagnosis of ESCC. Furthermore, analysis of miR-196a levels in saliva samples determined an average of 27-fold up-regulations in ESCC patients compared with healthy group. Our results suggest that salivary miR-196a may be a suitable noninvasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…It has also been reported that miR-196a inhibits cell apoptosis, and promotes cell proliferation and invasion by targeting the inhibitor of growth family member 5 in pancreatic cancer (21). Furthermore, Maru et al (18) reported that miR-196a is upregulated in esophageal adenocarcinoma, and Fendereski et al (9) described an overexpression of miR-196a in ESCC. However, to the best of our knowledge, few studies have examined the role of miR-196a in regulation of the ESCC phenotype, and the role of miR-196a in ESCC remains unclear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also been reported that miR-196a inhibits cell apoptosis, and promotes cell proliferation and invasion by targeting the inhibitor of growth family member 5 in pancreatic cancer (21). Furthermore, Maru et al (18) reported that miR-196a is upregulated in esophageal adenocarcinoma, and Fendereski et al (9) described an overexpression of miR-196a in ESCC. However, to the best of our knowledge, few studies have examined the role of miR-196a in regulation of the ESCC phenotype, and the role of miR-196a in ESCC remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…It has previously been reported that miRNA dysregulation is involved in the development and progression of cancer (6). Previous studies have revealed that miR-196a is upregulated in various types of cancer, including ESCC (7)(8)(9). Further studies have demonstrated that miR-196a promotes tumor progression and acts as an oncogene in some types of cancer (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Correlation of aberrant miR-196a expression and single nucleotide polymorphisms with chemosensitivity and radioresistance has been demonstrated in different studies, suggesting that investigating expression patterns and known polymorphisms might be useful in development of therapeutic strategies (29,30). Upregulation of miR-196a was previously shown in esophageal adenocarcinoma, in saliva specimens and ESCC cell lines (11,12,22). The alteration of miR-196a expression is in concordance with previous studies, but the lack of statistical significance as well as the non-significant relationship between expression changes and short survival could be due to the small sample size in our study.…”
Section: Correlation Analysis Of the Mir-196a With Clinicopathologicamentioning
confidence: 95%
“…Evidence suggests that expression of this microRNA may be altered in esophageal adenocarcinoma cancer cells. Moreover, it's up regulation has been recently discovered in the saliva specimens from ESCC patients and ESCC cell lines (11,12). It seems that the level of miR-196a expression is associated with metastasis, poor prognosis and reduced overall survival of the patients (13,14).…”
Section: Introductionmentioning
confidence: 99%
“… 3 Growing evidence shows that some miRs have a tumor-promoting or -suppressing function, and miR expression is aberrant in many kinds of malignant tumors, including ESCC. 4 , 5 Additionally, some cancer-related miRs are detectable and stable in body fluids, indicating the potential of circulating miRs as a new class of biomarkers for the early diagnosis, prognosis prediction, and therapeutic evaluation of patients with cancer. 6 , 7 For example, plasma miR-92a-2 has been identified as a noninvasive diagnostic biomarker for small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%